Short Communication Response of Rice to Zn Application Under Salt Affected Soil in Hafizabad District, Pakistan: Short Communication: Rice Response to Zn - Arshadullah, Muhammad; Ali, Arshad; Hyder, Syed Ishtiaq; Mahmood, Imdad Ali; Zaman, Badr-uz- (Biological Sciences - PJSIR, 2011)
The effect of different levels of Zn (0, 5, 10 and 15 kg/ha) was evaluated on growth and ionic concentration of rice variety (cv. CM.204 ) directly sown on raised bed under saline-sodic soil. Tillering, number of grains/spike, 1000 grain weight and paddy yield significantly (p = 0.05) increased with the increase in the rate of Zn application. Paddy yield was the maximum at the application of 15 kg Zn/ha, being 29% more than the control treatment. The maximum number of tillers/hill (62), number of grains/spike (121) and 1000 grain weight (26.40 g) were recorded with Zn application @ 15 kg/ha. The maximum paddy yield (7906 kg/ha) was attained @ 15 kg Zn/ha. The maximum Zn (45 ppm) in grain was determined from treatment receiving 15 kg Zn/ha followed by 10 kg Zn/ha (38 ppm).